Detroit five years after bankruptcy: From coercion to consent. (August 2021) - Barnes, Tom; Roose, Joshua M.; Turner, Bryan S.
Critical scholarship has characterised the 2013–2014 bankruptcy of Detroit – the largest municipal bankruptcy in history – as a fiscal 'state of exception' which undermined the democratic foundations of urban citizenship. From this perspective, the imposition of emergency management and declaration of bankruptcy were acts of raw coercion. Drawing upon Antonio Gramsci's theory of hegemony and empirical evidence, including interviews with civic leaders shortly after the bankruptcy, a survey of public attitudes towards the bankruptcy and public records from the bankruptcy court, this article charts a different interpretation of evolving public opinion in the five years post bankruptcy. We present evidence of a popular narrative among Detroiters which retroactively depicts the bankruptcy as a necessary evil, akin to a market clearing signal at the bottom of a business cycle. Far from bankruptcy being viewed as purely coercive, we suggest that this narrative has operated as an important mechanism of civic and political consent.